2022
DOI: 10.1007/s00259-022-05756-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumour PSMA intensity is an independent prognostic biomarker for biochemical recurrence-free survival following radical prostatectomy

Abstract: Purpose The prognostic value of PSMA intensity on PSMA PET/CT due to underlying biology and subsequent clinical implications is an emerging topic of interest. We sought to investigate whether primary tumour PSMA PET intensity contributes to pre- and post-operative prediction of oncological outcomes following radical prostatectomy. Methods We performed a retrospective cohort study of 848 men who underwent all of multiparametric MRI (mpMRI), transperineal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…Like this study, Goffin et al also found a relationship between prostate uptake and biopsy grade 11 . By comparison Roberts et al found a lower detection rate with Ga‐PSMA: 92% of 848 men with biopsy‐proven PC had primary lesions with SUV max ≥ 3 22 . In a meta‐analysis of Ga‐PSMA, Perera et al found that for men with Gleason score of ≤7 had a positivity of 72% compared with 80% in men with a Gleason sum of ≥8 23 .…”
Section: Discussionsupporting
confidence: 67%
“…Like this study, Goffin et al also found a relationship between prostate uptake and biopsy grade 11 . By comparison Roberts et al found a lower detection rate with Ga‐PSMA: 92% of 848 men with biopsy‐proven PC had primary lesions with SUV max ≥ 3 22 . In a meta‐analysis of Ga‐PSMA, Perera et al found that for men with Gleason score of ≤7 had a positivity of 72% compared with 80% in men with a Gleason sum of ≥8 23 .…”
Section: Discussionsupporting
confidence: 67%
“…The incorporation of imaging such as PSMA‐PET into clinical practice and the subsequent oncological outcomes can be captured by national registries and provide benchmarking for evidence‐based care [21]. Other considerations include different PSA thresholds to define BCR [22] or other imaging [23,24] or molecular tests [25]. For instance, molecular tests such as the Decipher ® genomic classifier, which is independently prognostic for major oncological outcomes (adverse surgical pathology, progression‐free survival, metastasis‐free survival and overall survival) for patients prior to or after RP may provide further prognostic information [26], and merit inclusion in prospective trials in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate logistic regression models established by SUVmax, intraprostatic PSMA-derived tumor volume (iPSMA-TV), and intraprostatic total lesion PSMA (iTL-PSMA) could be able to efficiently previse high-risk PCa with the sensitivity and specificity of 87.5% and 50%, 62.5% and 100%, and 87.5% and 100%, respectively. A study performed by Roberts that included 848 patients after radical prostatectomy found that the SUVmax value of PSMA imaging lesions was remarkably negatively correlated with biochemical recurrence-free survival (BRFS) ( 22 ). Gleason score (GS) was also negatively correlated with BRF, and SUVmax value was an independent predictor of BRFS in patients.…”
Section: Novel Molecular Imaging Methods For Pca Diagnosismentioning
confidence: 99%